Prediction of Groundwater Fluctuations Using Meshless Local Petrov-Galerkin Numerical Method in a Field Aquifer (Birjand Aquifer) - A. Mohtashami; S. A. Hashemi Monfared; Gh. Azizyan; A. Akbarpour (Numerical Methods in Civil Engineering)
The prediction of groundwater level fluctuations is one of the most remarkable issues in water resources management, especially in arid and semiarid regions. The present study uses a numerical meshless method, named meshless local Petrov-Galerkin, to predict the groundwater level over a ten-year period. This method makes up for the shortcomings of mesh-dependent methods and increases modeling accuracy significantly. The study site is the unconfined aquifer of the Birjand plain with 190 groundwater discharge wells. The groundwater head is predicted based on two scenarios. The first scenario is defined as the discharge rate increased by 10% compared to the year before. Due to this scenario, the groundwater level in the aquifer is significantly reduced, especially in the central part (in the location of piezometer No. 8) and southwestern part (in the location of piezometer No. 5) of the aquifer, where groundwater table experiences 11.74 m and 35.80 m drawdown, respectively over a 10-year period. In that area, the high density of groundwater wells is the main reason for the depletion of the aquifer. Within the second scenario, the effect of rainfall rate is assessed by decreasing it by 20% and increasing discharge rate of groundwater wells by 5% compared to the year before. The results of this scenario show that the declines of groundwater level in the southwestern and central parts of the aquifer around 14.81 m and 5.05 m, respectively during the considered ten-year period.